THE EFFECT OF HUMAN RESOURCE DEVELOPMENT ON THE PERFORMANCE OF REGIONAL FINANCIAL AND ASSET AGENCY EMPLOYEES IN SIDENRENG RAPPANG REGENCY - Ramadhani, Novi Fauziah; Kurnia M, Fakhruddin; Nirmasari, Dian (Jurnal Manajemen Dan Bisnis, 2024)
This research aims to determine whether there is an influence of Human Resources Development on the Performance of Regional Financial and Asset Agency Employees in Sidenreng Rappang Regency. The population in this study was 88 employees. The sample measurement technique uses the Slovin formula with a magrin error of 10%, so the number of samples used is 46 respondents. Selected through random sampling technique. Data was collected through questionnaires. The results of the analysis show that there is a positive and significant influence of Human Resource Development on Employee Performance, with the calculated t value (3.420) which is greater than the t table (2.017). Therefore, the hypothesis which states that there is an influence of Human Resource Development on Employee Performance can be accepted. With a coefficient of determination (r square) of 21.0%. shows that the validity of employee performance can be explained by Human Resources Development. While the rest is influenced by other factors outside the variables.